Drug utilization study in patients with type 2 diabetes mellitus attending diabetes clinic of a tertiary care hospital in rural Bengal - Mandal, Sekhar; Maiti, Tamoghna; Das, Asoke Kr.; Das, Abhijit; Mandal, Ananya; Sarkar, Biswanath Sharma; Mandal, Soumitra (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes mellitus (DM) is a common and important health problem affecting the citizens of developed as well as developing nations. Not only does it require long term therapy, it is also crippling in terms of cost of management. Drug utilization studies help to determine rational drug use especially in poorer and rural populations. The objective of this study was to evaluate drug utilization pattern in type-2 diabetes patients in a diabetic clinic of a tertiary care teaching hospital in rural Bengal. Methods: This was a prospective observational study including 181 patients for a period of 6 months in Bankura Sammilani Medical College. Patients diagnosed as type 2 diabetes mellitus were included in the study. The demographic data, disease data and utilization of different classes of oral hypoglycaemic agents and insulin as well as other individual drugs were analysed using the World Health Organization (WHO) indicators for drug utilization studies. Results: The study population was predominantly male (61.33%) and nearly a third (30.9%) belonged to the age group of 50-59 years. Co-morbid conditions were found in 74% patients, among which hypertension (51.1%) was the most common co-morbid condition. The average number of drugs per prescription was 4.22 and the average number of antidiabetic drugs per prescription was 2.18. Metformin was the most commonly prescribed drug (79.6%), followed by sulfonylurea class of drugs (66.9%). Nearly 17.7% patients were on insulin preparations. Glimepiride and metformin was the most common combinations used (45.5%). Antibiotics were included in 15.5% prescriptions and proton pump inhibitors were prescribed in 32% cases. All the medicines were prescribed as generics and injections were prescribed in 17.7% cases. Conclusions: This study gives a picture of the pattern of drug use among diabetes patients in our set up. While metformin was the commonest drug used, glimepiride and metformin combination was the commonest combination therapy.